The Victorian Nurse: gender and empire - Francisco Javier Castro Molina (Universidad de Alicante, 2017)
The emancipatory critique that characterized the Enlightenment was the tool that facilitated the presence of ideas such as equality, autonomy and solidarity. This broth was behind the emergence of a feminist movement that criticized the androcentric society that characterized the Victorian Era. The claims of the women focused on the right to vote and access to education that go beyond the elementary, ie the university. Major social changes that emerged from the Industrial Revolution, women joined the workforce. The struggle for equal was the catalyst for the emergence of the union, which sought to eliminate body models like the andropolítico that was established in England. The feminist ideology polluted every one of the structures that made up the various British authorities. Nursing, a discipline that until then had not consolidated as a profession was influenced by this movement. Florence Nightingale left clearly defined its position in the different publications that made the mid-nineteenth century. They define the role of the nurse and their relation to the figure of the doctor. In addition, Nightingale established a eulogy speech for equality with men, emphasizing the importance of training women.